Understanding the Determinants of Supermarket Loyalty Among Young People: A Case of Uganda Christian University Students - Esther Mutyaba (Uganda Christian University, 2024)
In thedynamic landscape of retail, supermarkets face an ongoing challenge in retaining customer loyalty. The phenomenon of customers frequently switching supermarkets poses difficulty to establishing a loyal client base. This issue is particularly pronounced among young consumers, exemplified by students from Uganda Christian University (UCU) who routinely engage with supermarkets in the Mukono region. To address this concern, an in-depth exploration is essential to unravel the intricacies of loyalty drivers specific to this demographic.